4.2 NETWORK CONNECTIVITY IN DISTINCT COGNITIVE SUBTYPES ACROSS THE PSYCHOSES - Lewandowski, Kathryn (Schizophr Bull, 2019)
BACKGROUND: Substantial cognitive heterogeneity exists both within and between diagnostic categories in patients with psychosis. Given that cognitive deficits are highly predictive of outcomes in patients and are believed to be underpinned by neurobiological abnormalities in relevant circuits, characterization of cognitive heterogeneity is a critical step toward understanding neurobiological and functional correlates of this key symptom dimension. Thus, we identified patients with psychosis with intact or impaired cognitive profiles, and examined clinical, functional, and resting state connectivity both between patient groups and compared to controls. We also compared findings in patients in the early course of illness versus chronicity to explore these associations across illness stages. METHODS: Patients with affective or non-affective psychosis (n=120) and healthy controls (n=31) were assessed using measures of cognition, clinical symptoms, and community functioning, and administered an fMRI scan to measure resting state functional connectivity (RSFC). Cognitive scores were used to group patients with and without cognitive dysfunction. Clinical, functional, and resting state data were compared between all three groups; RSFC data were examined controlling for demographic and clinical variables. RESULTS: Compared to controls, both cognitively intact and cognitively impaired patients showed decreased network connectivity in frontoparietal control and motor networks. Patients with cognitive impairment showed additional frontoparietal connectivity reductions compared to patients with intact cognition, particularly in subnetwork A, even after controlling for measures of illness severity (e.g. clinical symptoms, medication). Similar findings were detected in both early and chronic illness phases. CONCLUSIONS: Heterogeneity in cognitive ability among patients with psychosis can be leveraged to disentangle the relative effects of cognitive dysfunction and presence of an underlying psychotic illness using RSFC. Additionally, early and chronic patients showed similar patterns of association between cognition, network connectivity, and functioning. These findings suggest at least partially separable effects of presence of a psychotic disorder and neurocognitive impairment contributing to network dysconnectivity in psychosis that is detectable across illness stages.